Assessment of seroconversion against peste des petits ruminants vaccine among sheep and goats in Buchanan, Liberia (2012)
Serological response to a live commercial vaccine of Peste des petits ruminants (PPR) virus administered to sheep and goats in Buchanan, the capital city of Grand Bassa County, Liberia was assessed in view of its importance for effective restocking of small ruminants in the city. Forty-four paired serum samples (pre- and post-vaccination) were collected from vaccinated sheep and goats during a nation-wide campaign for food security promotion from March to October, 2011. Sheep and goats were vaccinated against PPR in late April, 2011. Pre-vaccination samples were collected in mid-April, 2011. Post-vaccination samples were collected in mid-October 2011 from the same groups of sheep and goats (6 months after vaccination). Paired serum samples gathered were stored at -4 0C until tested. Competitive Enzyme Linked Immunosorbent Assay (c-ELISA) was used to determine antibody levels against PPR virus. Only 34(77.3%) out of 44 paired serum samples were adequate in quantity and quality for the test. Test results indicated 27(79.4%) out of 44 paired serum samples increased significantly in antibody levels from pre-vaccination to post-vaccination levels that were equal or above threshold of Percentage Inhibition (PI > 50%) against PPR vaccine. The importance of these findings to effective veterinary services delivery for the control of this neglected animal disease in Liberia is discussed. The present seroconversion status against PPR virus is considered to be a milestone in rebuilding veterinary services systems in Liberia towards national efforts for food security after prolonged civil war (1989-2003) in the country.